Research on the energy efficiency indicators of transport diesel engines under transient operation conditions - Lebedevas, Sergejus (Array, 2018)
In this study, we have investigated the efficiency of transport diesel engines CAT3512B-HD in transient braking and acceleration modes in 2M62M locomotives. A comparative analysis of the diesel engine performance has been performed at speeds of power increase and braking ranging from 4–5 kW/s to 17–18 kW/s. A decrease in the fuel economy occurred, and the main reason for it (compared with the steady-state operating condition at qcycl = idem) has been found to be the deterioration of the mechanical efficiency coefficient due to the loss of the additional equipment kinetic energy of the engine. The efficiency decreased by 3–3.5% under power increase operations and by 10–14% in the braking modes. The original methodology for the evaluation of the diesel engine parameters registered by the engine control units (ECU) in the engine operating conditions, mathematical modelling application AVL BOOST, and analytical summaries in artificial neural networks (ANNs) have been used. The errors in the obtained results have been 5–8% at a determination coefficient of 0.97–0.99.